1988
DOI: 10.1111/j.1469-8749.1988.tb04779.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Cutaneous Flexor Reflex: Comparative Study of Preterm Infants and Newborn Rat Pups

Abstract: SUMMARY Cutaneous flexor reflex thresholds have been used as a measure of somatosensory function: the authors measured threshold in preterm infants and newborn rat pups. Preterm infants of less than 30 weeks postconceptional age (PCA) had very low thresholds of less than 1·0g, but by 37·5+ weeks PCA thresholds were equivalent to those in normal term babies, although these are still well below adult levels. Newborn rat pups also have very low flexor reflex thresholds, which do not approach adult levels until fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(70 citation statements)
references
References 22 publications
0
66
1
1
Order By: Relevance
“…Animal studies have shown an analgesic efect of sweet solutions during infancy similar to that of humans [52]. Sweet components of milk including sucrose, glucose or fructose have shown to alleviate neonatal pain [53,54].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%
“…Animal studies have shown an analgesic efect of sweet solutions during infancy similar to that of humans [52]. Sweet components of milk including sucrose, glucose or fructose have shown to alleviate neonatal pain [53,54].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%
“…In evaluating the dorsal cutaneous flexor withdrawal reflex, preterm infants have a third to 50% of the threshold for the dorsal cutaneous flexor reflex reaction to pain as compared to term infants. 13 The afferent limb of the withdrawal reflex is conducted by C-fibers, which are pain-conducting fibers. Term infants have a lower threshold for this reflex compared to older children or adults because there is a delayed maturation of descending inhibitory fibers.…”
Section: What Are the Sources Of Infant Pain?mentioning
confidence: 99%
“…Withdrawal thresholds increase as a function of age in both rats and humans (Reynolds and Fitzgerald 1995, Fitzgerald et al 1988, Andrews and Fitzgerald 1994. This reduction in sensitivity occurs during the normal course of development.…”
mentioning
confidence: 99%